Дослідження основних параметрів паперу для блокнота «TRAVEL BOOK» - Орленко, К. (My University, 2020)
In stationery, the paper is one of the hallmarks of practicality and durability. With the right choice of paper parameter values, it indicates the quality of the publication
Keywords: параметри паперу; папір; блокнот «TRAVEL BOOK»